Validation of Biochemical Markers for the Prediction of Liver Fibrosis and Necroinflammatory Activity in Hemodialysis Patients with Chronic Hepatitis C - (:unkn) unknown (KARGER, 2011)
Background: Liver biopsy is an imperfect gold standard for assessing the disease severity in hemodialysis patients with chronic hepatitis C. Our purpose was to compare the accuracy of the FibroTest (FT) and ActiTest (AT) with liver biopsy and the AST-to-platelet ratio index (APRI) in determining hepatic fibrosis and necroinflammatory activity in hemodialysis patients with hepatitis C virus (HCV). Methods: The FT-AT index combining 6 biochemical markers was assessed in 33 hemodialysis patients with HCV. Liver fibrosis and necroinflammatory activity was staged and graded according to the METAVIR scoring system. Results: The accuracy of FT-AT versus biopsy was 0.46 for significant fibrosis and 0.36 for severe necroinflammatory activity. The FT index had a positive predictive value of 20% for scores greater than 0.6 and a negative predictive value of 45% for scores less than 0.2. Eleven of the 33 patients had scores <= 0.2, 6 had significant fibrosis on biopsy. Four out of 5 patients with FT scores >0.6 had mild fibrosis. APRI correlated well with the biopsy. Conclusion: The FT-AT test does not seem to be a reliable noninvasive marker for the prediction of necroinflammatory activity and fibrosis in hemodialysis patients with HCV and cannot be used as an alternative to either liver biopsy or APRI. Copyright (C) 2010 S. Karger AG, Basel
Keywords: Hemodialysis; Chronic hepatitis C; FibroTest-ActiTest; Fibrosis; Necroinflammatory activity; METAVIR scoring; AST-to-platelet ratio index; VIRUS-INFECTION; BIOPSY; AMINOTRANSFERASE; FIBROTEST; ALANINE; LINE; HIV